2017
DOI: 10.1111/cge.13001
|View full text |Cite
|
Sign up to set email alerts
|

A novel DNAJB6 mutation causes dominantly inherited distal‐onset myopathy and compromises DNAJB6 function

Abstract: This study expands the molecular spectrum of DNAJB6 mutations and also emphasizes the pathogenic role of DNAJB6 dysfunction in distal-onset myopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…LGMD [89] c.287C>G p.P96R distal-proximal [86] c.287C>T p.P96L [100][101][102] c.293_295delATG p.D98del distal [89] c.298T>A p.F100I [103] c.298C>A p.F100V distal onset [88] c.346+5G>A p.G79_F115del severe, early onset [88] Reference sequences: NM_058246.4 (nucleotide), NP_490647.1 (protein).…”
Section: Pf93lmentioning
confidence: 99%
See 1 more Smart Citation
“…LGMD [89] c.287C>G p.P96R distal-proximal [86] c.287C>T p.P96L [100][101][102] c.293_295delATG p.D98del distal [89] c.298T>A p.F100I [103] c.298C>A p.F100V distal onset [88] c.346+5G>A p.G79_F115del severe, early onset [88] Reference sequences: NM_058246.4 (nucleotide), NP_490647.1 (protein).…”
Section: Pf93lmentioning
confidence: 99%
“…Dysphagia has been reported with several mutations [88][89][90]94,95,97,[101][102][103]. Respiratory involvement is rare, but patients with the severe p.F91I and p.F91L mutations had respiratory failure requiring mechanical ventilation [95].…”
Section: Clinical and Pathological Featuresmentioning
confidence: 99%
“…A), are those due to mutations in dysferlin ( DYSF ) (also called Myoshi myopathy) and anoctamin‐5 ( ANO5 ) . Also mutations in DNAJB6 initially affect the posterior compartment leg muscles; relative sparing of the tibialis anterior can be observed even in the setting of severe distal weakness . AD mutations in myotilin ( MYOT ) manifest clinically with foot drop or calf muscle weakness, but calf muscle involvement seems to occur first and can be documented radiologically, although it may not cause functional deficits until the anterior leg muscles become weak .…”
Section: Clinical Features and Underlying Gene Defectmentioning
confidence: 99%
“…The first French families with DNAJB6 mutations are presented. DNAJB6 mutations were first related to LGMD1D, but this and other recent studies have shown a wider phenotype and variable severity compared to the most frequent mutation, p.Phe93Leu [1][2][3][4][5][6]8,[13][14][15].…”
Section: Discussionmentioning
confidence: 81%
“…Autosomal dominant limb girdle muscular dystrophy type 1D (LGMD1D, OMIM 603511) caused by DNAJB6 mutations [1,2] has so far been identified in Europe [1,3,4], Asia [5][6][7][8] and the USA [1,2,9,10]. All reported mutations affect DNAJB6's G/F domain, encoded by exon 5.…”
Section: Introductionmentioning
confidence: 99%